Antioxidant test of crude extract of secondary metabolites from Fusarium sp. isolate of rizosphere of cat’s whisker - Piska, Finna; Zega, Sati Angriani; Hutauruk, Rico Halim; Septia, Evianti Dwi; Meutia, Rena (Jurnal Prima Medika Sains, 2024)
Antioxidants are compounds needed in the prevention and therapy of diseases such as diabetes mellitus, cancer and premature aging. Over time, secondary metabolite compounds as antioxidants can be obtained from microbes, namely those originating from the endophyte and rhizosphere of plants. Based on previous research, secondary metabolites that act as antioxidants are flavonoids and phenolics, with phenolic compounds and flavonoids can bind free radicals through hydroxyl groups present in their aromatic rings. Microbes that live on medicinal plants will have similarities in producing secondary metabolites which can also be used as medicine. Fusarium sp. Laboratorium Basic Science UNPRI (LBSU) isolate is an isolate isolated from the rhizosphere of the cat's whisker plant (Orthosiphon stamineus). The cat's whisker plant is known to be an antioxidant. This study aims to test the antioxidant crude extract of secondary metabolites from Fusarium sp. LBSU. The method for isolating secondary metabolites is by liquid fermentation, then extracted using ethyl acetate and tested for antioxidant activity using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The antioxidant test results were obtained from the DPPH radical inhibition value by Ethyl acetate Extract of Fusarium sp. LBSU (EEF) is 44%, while Vitamin C is 88%. Thus, the ability to capture DPPH free radicals by EEF is 44%, weaker than Vitamin C.